Structural deformation monitoring and numerical simulation of a supertall building during construction stage. (15th April 2020) - Gao, Fei; Zhou, Hong; Liang, Hongjun; Weng, Shun; Zhu, Hongping
Highlights: Massive monitoring data about a super high-rise building during construction were given. An FE model considering time-varying properties of materials and structures was established. The calculated values of the model agree well with the monitoring results. The structural deformation under different actual constructional condition was analyzed. Abstract: The time-varying characteristics of concrete materials result in additional deformation which cannot be fully considered in the design stage. The deformation will be greatly magnified for supertall buildings due to the long construction period and complex construction processes. To assess the impact of such characteristics, this study conducted structural deformation monitoring and a numerical analysis of a 335 m-tall building. The real-time vertical deformation of several typical floors were monitored by 128 vibrating wire strain gauges during construction stage from the 10th floor to the 48th floor. The on-site monitoring data were then compared with the finite element (FE) results calculated by a Midas FE model, which considered construction speed, time-varying characteristics of concrete materials and the whole structure. Comparison of deformations showed that the outcome of the FE analysis is consistent with the monitoring data. The verified FE model was then implemented to analyse structural deformation under different actual constructional conditions, including different construction qualities of concrete, construction shutdown and different relative humidity ( RH ) conditions. Numerical results revealed that the construction quality of concrete has a large nonlinear influence on vertical deformation. When the shutdown time exceeds three months, the construction levelling plan should be updated as the construction restarts. The effect of RH values in different seasons on the shrinkage and creep of concrete is huge and important to consider for vertical deformation of supertall buildings.